2020
DOI: 10.1167/iovs.61.3.54
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-α Agonist Fenofibrate Suppressed the Formation of Ocular Surface Squamous Metaplasia Induced by Topical Benzalkonium Chloride

Abstract: Purpose To investigate the effects and mechanisms of the peroxisome proliferator-activated receptor alpha (PPAR-α) agonist fenofibrate on the formation of ocular surface squamous metaplasia induced by topical benzalkonium chloride (BAC) in a mouse model. Methods Ocular surface squamous metaplasia was induced in 16 days by topical BAC application in mice. During the period of induction, mice were divided into four groups: no additional treatment (BAC+UT), topical vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Even though there are not many reports available on the roles of PPARα in the ocular surface, recent evidence suggests that PPARα may play a critical role in the regulation of inflammatory processes in the ocular surface [ 107 ]. Fenofibrate ameliorated the severity of ocular surface squamous metaplasia, commonly seen in patients with long-term deficiency of tear film [ 108 ] and suppressed the formation of tear film instability via the inhibition of macrophages and downregulation of pro-inflammatory factors [ 107 ]. In the corneal epithelium of mice with dry eyes by sleep deprivation, downregulation of PPARα expression was detected [ 109 ], and fenofibrate increased PPARα expression in cultured corneal epithelium sheets and restored microvilli morphology [ 109 ].…”
Section: Functions Of Pparα In the Eyementioning
confidence: 99%
“…Even though there are not many reports available on the roles of PPARα in the ocular surface, recent evidence suggests that PPARα may play a critical role in the regulation of inflammatory processes in the ocular surface [ 107 ]. Fenofibrate ameliorated the severity of ocular surface squamous metaplasia, commonly seen in patients with long-term deficiency of tear film [ 108 ] and suppressed the formation of tear film instability via the inhibition of macrophages and downregulation of pro-inflammatory factors [ 107 ]. In the corneal epithelium of mice with dry eyes by sleep deprivation, downregulation of PPARα expression was detected [ 109 ], and fenofibrate increased PPARα expression in cultured corneal epithelium sheets and restored microvilli morphology [ 109 ].…”
Section: Functions Of Pparα In the Eyementioning
confidence: 99%
“… 24 , 25 A recent study, including topical application of fenofibrate to dry eye model induced by benzalkonium chloride, showed an improvement in ocular surface staining, tear film breakup time, and a reduction in inflammatory response in the cornea. 26 Moreover, He et al 27 reported that fenofibrate might provide therapeutic benefit in dry eye induced by hyperlipidemia. However, no prior study has focused on the effect of fenofibrate on SS-associated dacryoadenitis.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 42 By activating PPAR-α, fenofibrate increased the gene expression of Foxp3 in isolated CD4 + T cells from EAM rats 33 and decreased corneal epithelial staining scores in a dry eye model induced by topical benzalkonium chloride. 26 In addition, fenofibrate has also been found to inhibit nitric oxide synthase (iNOS) expression and nitric oxide (NO) release in infected cardiomyocytes in a PPARα-independent manner. 43 In our study, we found that after fenofibrate treatment, the protein and mRNA levels of PPAR-α were significantly higher, suggesting that fenofibrate might ameliorate LG inflammation via its PPAR-α agonistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased expression level of PPARα had been found to be associated with retinal inflammation and choroidal neovascularization (Abcouwer, 2013;Chen et al, 2013). In recent years, lots of studies showed that PPARα agonists exert therapeutic effects against ocular degenerative disorders with effects on anti-inflammatory, anticoagulant, anti-apoptosis, antioxidation and inhibition of neovascularization (Deng et al, 2017;He et al, 2020;Nakano et al, 2020;Nakano et al, 2020), while PPARα−/− mice with diabetes manifest more severe retinal acellular capillaries (Moran et al, 2014;Qiu et al, 2017). It was also demonstrated that PPARα plays a critical role in the regulation of inflammatory process and squamous metaplasia in ocular surface (He et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, lots of studies showed that PPARα agonists exert therapeutic effects against ocular degenerative disorders with effects on anti-inflammatory, anticoagulant, anti-apoptosis, antioxidation and inhibition of neovascularization (Deng et al, 2017;He et al, 2020;Nakano et al, 2020;Nakano et al, 2020), while PPARα−/− mice with diabetes manifest more severe retinal acellular capillaries (Moran et al, 2014;Qiu et al, 2017). It was also demonstrated that PPARα plays a critical role in the regulation of inflammatory process and squamous metaplasia in ocular surface (He et al, 2020). In addition, PPARα agonists had therapeutic effects against corneal neovascularization induce by alkali burn or FGF2 (Panigrahy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%